(untitled) (Географический вестник=Geographical bulletin, 2017)
Приведены результаты численного анализа облачных структур по данным метеорологических радиолокаторов и метеорологических спутников Земли. Разработана методика комплексного анализа данных МРЛ и МСЗ, определены радиолокационные и спутниковые характеристики облачности, проанализированы суточный и годовой ход форм облачности, выявлены мезоструктурные особенности. Mesostructural peculiarities of the atmospheric front according to the radar and sputnik information Results are presented of numerical analysis of cloudiness fields during the year on a fine grid based on objectively matching of radar and sputnik measurements. A classification of mesoscale cloud fields of radar and sputnik measurement for days, months and seasons is presented. The investigation with the use of the composite (complex) approach leads to the conclusion that mesoscale g atmospheric processes are deterministic by mesoscale b circulations. Regular existence of such circulations against processes of larger scales determines the predictability of mesoscale g processes. Here from, it is possible to combine existing classifications of the convective cloud evolution and to use deterministic methods in the very short-range weather forecasting.